(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2022)
The purpose of this study is to compare Over-The-Top (OTT) and Internet Protocol Television (IPTV) services, the former consists of the transmission of audio, video and other types of content over the Internet, while the IPTV service is the one that transmits audio and video over IP protocols. The advantages of OTT and IPTV technological systems, protocols for their operation, and a brief review of the hardware required for implementation are presented. The methodology used in the study is bibliographic documentary, the information obtained for the constitution of the conceptual theoretical framework was obtained from specialist. The results allow to evidence that in Ecuador most citizens have a TV and smartphone in their homes, more than half of the population has Internet connection permanently, the evolution of the use of OTT and IPTV exacerbated by the confinement due to the health emergency, are inputs that allow us to conclude that video streaming services: OTT and IPTV constitute an alternative for users, due to the accessibility they present of the content to the user.